Crosstalk between the Gut and Brain in Ischemic Stroke: Mechanistic Insights and Therapeutic Options - Wenjing Huang; Luwen Zhu; Wenjing Song; Mei Zhang; Lili Teng; Minmin Wu (Mediators of Inflammation)
There has been a significant amount of interest in the past two decades in the study of the evolution of the gut microbiota, its internal and external impacts on the gut, and risk factors for cerebrovascular disorders such as cerebral ischemic stroke. The network of bidirectional communication between gut microorganisms and their host is known as the microbiota-gut-brain axis (MGBA). There is mounting evidence that maintaining gut microbiota homeostasis can frequently enhance the effectiveness of ischemic stroke treatment by modulating immune, metabolic, and inflammatory responses through MGBA. To effectively monitor and cure ischemic stroke, restoring a healthy microbial ecology in the gut may be a critical therapeutic focus. This review highlights mechanistic insights on the MGBA in disease pathophysiology. This review summarizes the role of MGBA signaling in the development of stroke risk factors such as aging, hypertension, obesity, diabetes, and atherosclerosis, as well as changes in the microbiota in experimental or clinical populations. In addition, this review also examines dietary changes, the administration of probiotics and prebiotics, and fecal microbiota transplantation as treatment options for ischemic stroke as potential health benefits. It will become more apparent how the MGBA affects human health and disease with continuing advancements in this emerging field of biomedical sciences.